CSF neurofilament light chain testing as an aid to determine treatment strategies in MS. Issue 6 (November 2020) - Reyes, Saúl; Smets, Ide; Holden, David; Carrillo-Loza, Karina; Christmas, Tatiana; Bianchi, Lucia; Ammoscato, Francesca; Turner, Benjamin; Marta, Monica; Schmierer, Klaus; Giovannoni, Gavin; Gnanapavan, Sharmilee
Abstract : Objective: To evaluate the use of CSF neurofilament light chain (NfL) measurements in clinical practice as well as their effect on treatment strategies and outcomes in patients with MS. Methods: This was an observational cohort study of patients with MS who had a CSF NfL measurement between December 2015 and July 2018 as part of their routine clinical care. Treatment strategies were classified as "No Treatment/No Escalation" (no treatment or no escalation of treatment) or "Treatment/Escalation" (first-line injectable/oral disease-modifying therapies (DMTs), highly active DMTs, or treatment escalation). Change in Expanded Disability Status Scale (EDSS) scores was evaluated after 1-year follow-up. Results: Of 203 patients with MS, 117 (58%) had relapsing-remitting MS. Disease activity was most frequently indicated by elevated CSF NfL (n = 85), followed by clinical (n = 81) and MRI activity (n = 65). CSF NfL measurements were independently associated with clinical ( p = 0.02) and MRI activity ( p < 0.001). Of those with elevated CSF NfL as the only evidence of disease activity (n = 22), 77% had progressive MS (PMS). In patients with PMS, 17 (20%) had elevated CSF NfL as the sole indicator of disease activity. Elevated CSF NfL resulted more frequently in Treatment/Escalation than normal CSF NfL ( p < 0.001). Median EDSS change at follow-up was similar between patients receiving No Treatment/No Escalation and Treatment/Escalation decisions ( p = 0.81). Conclusions: CSF NfL measurements informed treatment strategies, alongside clinical and MRI measures. CSF NfL levels were the only indicator of disease activity in a subset of patients, which was more pronounced in patients with PMS. Elevated CSF NfL was associated with more Treatment/Escalation strategies, which had an impact on EDSS outcomes at 1 year.